Need Analysis for Ecological Consciousness to Improve Metacognitive Awareness for Students in Islamic Learning - Demina; Ramli, Syahrur; Susrizal, Silvia; Zakia, Nadia; Khadafi, Muhammad (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study explores the integration of ecotheology into Islamic Religious Education (PAI) to enhance metacognitive awareness among students. Given the increasing ecological crisis, particularly in Indonesia, this research addresses the gap between students' cognitive understanding of environmental issues and their moral responsibility towards nature. Using a qualitative approach, interviews were conducted with 94 12th-grade students at MAN 2 Tanah Datar, West Sumatra, to assess their needs for combining ecological consciousness with metacognitive skills. The findings indicate that 71.5% of students require integrative knowledge that merges ecological awareness with metacognitive strategies. In comparison, 55.5% express the need for structured learning steps and regulations to effectively connect these areas. The results suggest that a two-month learning process is necessary to cultivate meaningful metacognitive understanding through ecotheological integration. This study highlights the importance of fostering reflective thinking and self-regulation in students to bridge the gap between theoretical ecological knowledge and real-life behaviors. However, the study is limited by its focus on a single institution and the use of only two metacognitive indicators. Future research should expand to include a broader range of metacognitive aspects and explore the integration of ecotheology in diverse educational settings to enhance students' ecological consciousness and critical thinking skills.